Assessing University Students’ Self-Reported Vocabulary Learning Strategy Use - Girma, Yirgalem; Tesema, Ermias Mulat; Berhanu, Yeneneh Wubetu (Journal of learning theory and methodology (Online), 2025)
Background. Learning vocabulary is a vital component of language learning; without this integral component of language communication becomes hardly meaningful. Thus, students are expected to have rich vocabulary power that enables them to communicate successfully via listening, speaking, reading, and writing; it assists students in expressing a range of meanings in various communicative situations for various purposes. This demands students to learn vocabulary using diverse vocabulary learning strategies that assist them in learning (internalizing, storing, recalling, and using) words properly. However, several students barely manage vocabulary learning tasks and/or use appropriate and diverse vocabulary in English classes. Objectives. This study attempted to assess students’ reported vocabulary learning strategy used at Haramaya University, Ethiopia. Materials and methods. The study adopted a descriptive case study design. The five-point Likert scale vocabulary learning strategy questionnaire was administered to participants taking Communicative English skills I. To gather relevant data, 155 participants were randomly selected. Out of the 155 students, 151 participants properly filled out the questionnaire. The data were analyzed using SPSS version 24. Results. The results indicated that determination, metacognitive, memory, cognitive, and social strategies were used, respectively. The results further showed that the great majority of the students were aware that inadequate vocabulary hinders students’ listening, speaking, reading, and writing skills. Conclusions. Overall, determination and meta-cognitive strategies were most commonly used, while the social strategies were least commonly used, and the participants were low-vocabulary learning strategy users.